Design of passive UHF RFID sensor on flexible foil for sports balls pressure monitoring. Issue 14 (3rd September 2018) - Rennane, Ahmed; Abdelnour, Abanob; Kaddour, Darine; Touhami, Rachida; Tedjini, Smail
Abstract : A simple solution to efficient pressure measurement in sports balls using a force sensitive resistance sensor connected to an ultra high frequencies (UHF) radio frequency identification (RFID) tag is presented. The proposed solution has the advantage of increasing the pressure range measurement without changing the configuration of the employed RFID chip. It also offers a small and compact sensor structure due to miniaturised antenna design. The designed antenna is placed between the ball inner and outer layers. Prototypes were fabricated on a flexible substrate to make their integration easy into a sport ball. This smart tag concept was fully validated through measurements on different types of sports balls, and the results successfully compared to data from electronic ball pressure gauge.